Evaluation of the collection of the Asian Center Library, University of the Philippines - Dizon, Cecilia M. (1982)
The study was undertaken to identify the strength and weaknesses of the Asian Center Library collection as perceived by the faculty and student clientele as well as to evaluate the Asian Center Library collection in terms of standard bibliographies in the field and Asian collections in some research and academic libraries abroad.